1999
DOI: 10.1902/annals.1999.4.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis

Abstract: The purpose of this review was to assess the scientific and clinical bases for the proposed classification of periodontitis. The clinical and histopathological signs and the etiology of periodontitis were described. Cross-sectional studies were analyzed to determine when onset of periodontitis most frequently occurs in adults. In addition, the progression rates of periodontitis have been assessed from longitudinal studies. No clinical, histopathological, or microbiological features could be identified that wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
302
0
41

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(343 citation statements)
references
References 69 publications
0
302
0
41
Order By: Relevance
“…However, the H. pylori status was not associated with AD in a study from Japan, probably due to the high prevalence of the organism in controls (84,87). Furthermore, the composition of the oral microbiota irrespective of being indigenous or pathogenic in the oral cavity keeps changing in view of major oral diseases (caries, gingivitis, aggressive and chronic periodontitis, periodontal-endodontic lesions, peri-implantitis and mucositis) (88)(89)(90)(91)(92)(93)(94).…”
Section: The Extrinsic Modelmentioning
confidence: 99%
“…However, the H. pylori status was not associated with AD in a study from Japan, probably due to the high prevalence of the organism in controls (84,87). Furthermore, the composition of the oral microbiota irrespective of being indigenous or pathogenic in the oral cavity keeps changing in view of major oral diseases (caries, gingivitis, aggressive and chronic periodontitis, periodontal-endodontic lesions, peri-implantitis and mucositis) (88)(89)(90)(91)(92)(93)(94).…”
Section: The Extrinsic Modelmentioning
confidence: 99%
“…Klasyfikacja z 1999 r. wyróżniła 2 główne postacie choroby: przewlekłe (chronic periodontitis, CP) i agresywne zapalenie przyzębia (aggressive periodontitis, AgP) [3]. CP było opisane jako choroba wolno postępująca (wcześniej była nazwana zapaleniem przyzębia dorosłych), która u niektó-rych pacjentów może przebiegać z krótkimi okresami szybkiej destrukcji.…”
Section: Przewlekłe a Agresywne Zapalenie Przyzębiaunclassified
“…W klasyfikacji z 1999 r. postać zlokalizowaną i uogólnioną rozróżniano na podstawie odsetka miejsc badanych objętych zmianami [3]. Postać zlokalizowana miała dotyczyć pacjentów, u których stwierdza się do 30% miejsc badanych objętych zmianami, natomiast w postaci uogólnionej zmiany patologiczne obejmowały więcej niż 30% miejsc badanych.…”
Section: Zlokalizowane a Uogólnione Zapalenie Przyzębiaunclassified
“…Chronic periodontitis has recently been defined as"an infectious disease resulting in inflammation within the supporting tissues of the teeth, progressive attachment loss, and bone loss." 1 The role of periodontal disease in the etiology of cardiovascular disease (CVD) has recently received considerable attention. Epidemiological studies have shown that there is elevation of the systemic inflammatory markers related to cardiovascular diseases in the peripheral blood of periodontitis patients.…”
Section: Introductionmentioning
confidence: 99%